Modeling of Human Potential Parameters in the Context of Innovation and Technological Development of the Country: Case of Asia-pacific Countries - Kuznetsova, Natalia Victorovna; Kocheva, Ekaterina Victorovna; Matev, Nikolay Anatolievich (International Journal of Economics and Financial Issues, 2016)
In this study, human capital is considered as a key factor for the innovative development of the country. The authors proposed an empirical model of the impact of human development on innovation and technological development of the country. Due to the high differentiation of the Asia-Pacific region, classification of countries, which was taken into account later when constructing the regression model, was carried out by defining the object of study indicators. Keywords: Asia-Pacific region, human capital, innovations, patents, econometric modeling. JEL Classifications: O, O15